Judging war crimes and torture : French justice and international criminal tribunals and commissions (1940-2005) - Beigbeder, Yves (Martinus Nijhoff, 2006)
Even democracies commit war crimes. France has long ignored its colonial crimes, only denounced by a few courageous opponents and revealed in trials. France is not the only democracy to have violated international humanitarian law. However, these violations must be exposed, so that they are not repeated.